Methodical support of SB RAS libraries network activity: an alternative variant of development - T. V. Dergileva (Библиосфера, 2014)
The paper examines the causes of changes in relationships between the SPSTL SB RAS, as a coordinating-methodical center, and the library network of SB RAS. More than fifty years SPSTL SB RAS has been providing organizational, managerial and administrative functions in relation to libraries of the network. Consequently, there were hierarchical relationships among them with the leading role of SPSTL SB RAS. In 2008 the labor legislation changed, and a new legal situation appeared. Development of the Internet and information technologies has contributed to the establishment of equal relationships of all participants of the integration processes in the electronic environment. In 2013 the Russian Academy of Sciences reforming began: one of the main directions - the centralized acquisition of libraries carried by SPSTL SB RAS - was canceled. Under current conditions the concept of organization of scientific-methodical activity of SPSTL SB RAS has changed. The transition from «top-down» scientific-methodical support of SB RAS library network to «bottom-up» methodical counseling implemented in depending on the needs of libraries according to their requests has taken place. Methodical counseling is typical for modern organization of librarianship of the most foreign countries.